PI3K/AKT pathway regulates phosphorylation of steroid receptors, hormone independence and tumor differentiation in breast cancer - Riggio, Marina (2012)
Using a model of medroxyprogesterone acetate (MPA)-induced mouse mammary tumors that transit through different stages of hormone dependence, we previously reported that the activation of the phosphatidylinositol 3-kinase (PI3K)/AKT (protein kinase B) pathway is critical for the growth of hormone-independent (HI) mammary carcinomas but not for the growth of hormone-dependent (HD) mammary carcinomas. The objective of this work was to explore whether the activation of the PI3K/AKT pathway is responsible for the changes in tumor phenotype and for the transition to autonomous growth. We found that the inhibition of the PI3K/AKT/mTOR (mammalian target of rapamycin) pathway suppresses HI tumor growth. In addition, we were able to induce mammary tumors in mice in the absence of MPA by inoculating HD tumor cells expressing a constitutively active form of AKT1, myristoylated AKT1 (myrAKT1). These tumors were highly differentiated and displayed a ductal phenotype with laminin-1 and cytokeratin 8 expression patterns typical of HI tumors. Furthermore, myrAKT1 increased the tumor growth of IBH-6 and IBH-7 human breast cancer cell lines. In the estrogen-dependent IBH-7 cell line, myrAKT1 induced estrogen-independent growth accompanied by the expression of the adhesion markers focal adhesion kinase and E-cadherin. Finally, we found that cells expressing myrAKT1 exhibited increased phosphorylation of the progesterone receptor at Ser190 and Ser294 and of the estrogen receptor α at Ser118 and Ser167, independently of exogenous MPA or estrogen supply. Our results indicate that the activation of the PI3K/AKT/mTOR pathway promotes tissue architecture remodeling and the activation of steroid receptors.